Corpo e poder em acampamentos educativos de lazer para adolescentes - Viviani, Maria Cristina Simões (2018)
Educational camps are companies that offer leisure services for teenagers during school vacations. They have the particularity of promoting a service where teenagers are deeply involved in the activities, in a place focused on the social interaction of individuals from the same age group, through the mediation of the camp's facilities and counselor's supervision and without the presence of their parents. I have the goal to understand, based on the dialogue with the teenagers' perception that go to this place, how they experience and build their notions regarding the body and the implications that those notions have for them. I sought to understand the negotiations and power struggles between campers and their counselors by analyzing which reasons led to questioning and confrontation. Therefore demonstrating how they produce and compare the adult meanings and the camp's control over the body and what it means for the relations of power.